Pemodelan Banjir Alur Baru Kali Kebo, Bengawan Solo - Regina Betalia; Legowo Wignyo Darsono; Waluyo Hatmoko (Journal on Education, 2024)
The New Kali Kebo Channel is a diversion from the old Kali Kebo Channel located in the Sub-Watershed of Watu Burik, a part of the Bengawan Solo Watershed. The purpose of this channel diversion is to meet land requirements for the construction of the Putri Cempo Waste-to-Energy Power Plant (PLTSa), aiming for a unified land area and facilitating ease of PLTSa operation. This diversion has the impact of a longer, wider, and deeper channel, leading to changes in river slope and flow velocity. The changes in hydraulic characteristics can lead to alterations in the river's cross-sectional capacity and the bank discharge of the river. The new channel employs non-erodible L-Gutter structures to prevent organic content from waste fermentation from entering the river. The river's waste content has the potential to alter river morphology due to the addition of suspended sediment discharge. The results of 1D and 2D unsteady flow modeling using the HEC-RAS model with a Q25-year discharge indicate significant overflow heights at the L-Gutter outlet, reaching a height of approximately ±20-30 cm.